FRI0496 Does long distance running cause joint effusion of the knees and ankles? the munich marathon experience. (23rd January 2014) - Proft, F.; Schramm, M.; Mueller, F.; Kriegmaier, M.; Schulze-Koops, H.; Grunke, M.; Reindl, C. S.
Abstract : Background: The effect of extreme physical exercise on joint effusions is unclear. Previous data are controversial concerning the impact of physical exercise on joint structures. Objectives: An ultrasound (US) evaluation was performed to investigate if long distance running causes effusion of knees and ankles and enthesitis or tendovaginitis of the patellar tendon or of the tendons around the ankles. Methods: 119 participants of the Munich Marathon, performing a full distance or half distance marathon in October 2012 were included in the study. Ultrasound examination of both knees and ankles was performed with a gray scale grading from 0-3 between 48 and 16 h before the event (baseline (BL)). In addition, the medial and lateral tendons of the ankles were examined for tendovaginitis and both patellar tendons were examined for enthesitis with power-doppler. The participants were asked to fill out a questionnaire about age, bodyweight, workout and arthralgia or joint swelling. Immediately after the longdistance run a second ultrasound examination of the same structures was performed (follow-up (FU)) and the participants were asked to fill out a second questionnaire about their complaints during the run. Results: 105 runners completed both ultrasound examinations and questionnaires (61 marathon and 44 half marathon runners). 210 knees were examined, 98 joints (47%) showed an effusion at BL. At follow-up 98 joint effusions were found (p > 0.05). No changes were seen in 135 knees (64%) between BL and FU. In 75 knees (36%), an alteration was detected at FU with 39 knees showed a new or progressive (3 knees) joint effusion, and 36 knees with effusion at BL showed regressive (2 knees) or no effusion any more. Enthesitis of the patellar tendon was detected by power-doppler in one knee at BL and persisted at FU, while new enthesitides at this location were found in 20 examinations (p < 0.001). Of 210 examined ankles, 38 showed an effusion at BL. At FU, 32 ankles with effusion were counted (p > 0.05). 173 (82%) ankles showed a stable finding at BL and FU, while in 37 an alteration was detected. 15 joints showed a new or progressive (1 ankle) effusion, 22 ankles with effusion at BL showed regressive (3 ankles) or dissolved effusion at FU. Only one medial tendovaginitis was detected at FU. Conclusions: Long distance running does not cause joint effusion in knees or ankles or tendovaginitis of the ankles´ tendons, but a significant increase of enthesitides of the patellar tendons. Disclosure of Interest: None Declared